Spatial integration of cereal markets in Ethiopia - Tamru, Seneshaw (International Food Policy Research Institute, 2013)
This study looks at the extent of and changes in spatial integration of cereal markets in Ethiopia over the last ten years. Based on weekly wholesale prices of the Ethiopian Grain Trade Enterprise (EGTE) and covering all major cereals in the country (three major types of teff [i.e., white, mixed, and red], white wheat, maize, and white sorghum), spatial integration of Addis Ababa with the most important regional wholesale markets in the country is analyzed. The estimation results indicate market integration has considerably improved over the last ten years for teff, wheat, and maize with faster price adjustments and lower estimated transaction costs. On the other hand, for white sorghum integration of regional markets with Addis Ababa did not improve over the last decade.